Effect of solvents on ZIF-8 and its adsorption efficiency for Norfloxacin - Wu, Li Li; Tan, Huey Ling; Lim, Ying Pei (Universiti Teknologi MARA, Perlis, 2025)
In this study, ZIF-8, a novel adsorption material for norfloxacin (NOR) adsorption, was created and evaluated. This study aimed to investigate the effect of using different solvents – water and methanol during the synthesis process on the adsorption performance of ZIF-8 towards NOR. Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscope (SEM) coupled with Energy Dispersive X-ray (EDX), Brunauer-Emmett-Teller (BET) and X-ray Diffractometer (XRD) studies were used to fully evaluate the synthesized adsorption material in order to comprehend its adsorption capabilities and structural characteristics. The findings indicated that ZIF-8 synthesized using methanol (ZIF-8-M) demonstrated superior crystallinity, greater pore volume, and a larger surface area when compared to ZIF-8-W, which was produced using water. Additionally, ZIF-8-W had a non-uniform particle structure with grain sizes of approximately 50.19±6.40 nm, while ZIF-8-M exhibited a uniform morphology with grain sizes around 12.62±1.11 nm. The adsorption experiments demonstrated that ZIF-8-M exhibited superior removal efficiency (86.4%) and adsorption capacity (17.30 mg g⁻¹) for NOR, while ZIF-8-W achieved lower values of 53.01% and 10.60 mg g⁻¹, respectively. In addition, isotherm studies demonstrated that both materials exhibited multilayer adsorption, with the Freundlich model best fit their adsorption behaviour. Using kinetic analysis, a pseudosecond-order model that suggested a chemical adsorption process was verified. Higher temperatures favoured adsorption, based on thermodynamic study, which also identified the spontaneous and endothermic process. This research underscores the importance of solvent choice during the synthesis process, which can significantly affect the properties of ZIF-8. The findings provide an improved comprehension of how solvents and ZIF-8 interact, which could lead to more efficient solutions for mitigating pharmaceutical pollution in wastewater systems.